Switched-boost-modified Z-source inverter topologies with improved voltage gain capability - Ahmad A.; Bussa V.K.; Singh R.K.; Mahanty R. (My University, 2025)
This paper presents three-phase switched-boost-modified Z-source inverter (ZSI) topologies with improved boost capabilities. In the proposed ZSIs, the voltage gain is increased significantly by adding one auxiliary switch and one diode without using additional passive components. The concept is applied to traditional ZSI, discontinuous input current quasi-ZSI (DC-qZSI), and continuous input current qZSI (CC-qZSI) resulting into three new inverter topologies: switched-boost ZSI, DC-qZSI, and CC-qZSI. Anatomization of operating principle, steady-state analysis, voltage gain, voltage stress, current stress, stored energy analysis, power loss, total harmonic distortion, and efficiency analysis are carried out to highlight the advantages of the proposed inverters as compared to the conventional ZSIs. Finally, the operation of the proposed CC-qZSI is validated through simulation and experimental results. © 2013 IEEE.